Development and milestones of alternating current hydraulic drives - Fekete, Tamás (Design of Machines and Structures, 2024)
The energy transfer at the hydraulic drives can be solving with direct current hydraulic drives and alternating current hydraulic drives. At the direct current hydraulic drives, the operating fluid flow in one way besides the alternating current hydraulic drives, where it is alternating periodically between the hydrogenerator and the hydromotor. In this research, I would like to examine the evolution and milestones of this scientific field.